2017
DOI: 10.1007/978-981-10-4086-3_35
|View full text |Cite
|
Sign up to set email alerts
|

Images Digitization and Characterization of Surface and Fundus obtained through a Slit Lamp Adapted

Abstract: Abstract-Slit Lamp (SL) is the equipment commonly used in most eye clinics. This instrument allows to observe ocular structures of both the anterior segment and posterior segment with different magnification values. Currently is very common obtain images from SL with a Smartphone (for documentation purposes) by means of a simple adapter in the eyepiece. These images lose their diagnostic quality due to the information lose to correct the lack correction of optical aberrations and noise introduced by this syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The main design of a conventional SLM does not include an image acquisition module. The digital image is obtained from the SLM using a camera or smartphone by means of an adapter in the eyepiece [11][12][13][14]. C. Yen et al reported a method of image acquisition from a smartphone with an SLM via a simple adapter in the eyepiece [13].…”
Section: Introductionmentioning
confidence: 99%
“…The main design of a conventional SLM does not include an image acquisition module. The digital image is obtained from the SLM using a camera or smartphone by means of an adapter in the eyepiece [11][12][13][14]. C. Yen et al reported a method of image acquisition from a smartphone with an SLM via a simple adapter in the eyepiece [13].…”
Section: Introductionmentioning
confidence: 99%